ركائز أسلمة المعرفة في تربية الأولاد: قصة لقمان وابنه أنموذجا: The pillars of the Islamization of knowledge in raising children: The story of Luqman and his son as a model - Mohammad Asri, Mohammad Afifi; Ahmad H. Osman, Rahmah; Ahmad Borhan, Ahmad Badri; Safin, Muhammad Mamdouh (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
ملخص التربية من الأشياء المهمة في حياة الفرد. وطريقة التربية التي يحصلها الشخص ستشكل بالتأكيد طريقة تفكيره وسلوكه. فلذلك، تعد التربية أمرا مهما، ويجب الاهتمام بها بشكل خاص لتكوين الفرد ليكون نافعا. إن التربيّة لا تنطوي فقط على الجانب الجسدي بل أيضًا تشتمل على جوانب أخرى كالروح والفكر. إن المشكلة الكبيرة لدى المجتمع في هذا العصر هي سقوط الأخلاق لدى الأبناء. فشل الأب والأم في تربية أولادهم بإتباع الطريقة الإسلامية المذكورة في القرآن في سورة لقمان. وتهدف هذه المقالة لوضع حلول لهذه المشكلة بالتعرف على أسلوب أسلمة المعرفة والتي استخدمها لقمان لتربية ولده من خلال النصائح التي أمره بها وجاءت في ثنايا السورة. Abstract Education is one of the most important things in a person's life. The way a person gets upbringing will certainly shape his way of thinking and behaviour. Therefore, education is an important aspect, and special attention must be paid to the formation of the individual with the best man. Education is an element that not only involves the physical aspect, but also emphasizes other aspects such as the spirit and the intellect. The big problem with society in this era is the fall of morals in children. The father and mother failed to raise their children following the Islamic way mentioned in the Qur’an in Surat Luqman. This article aims to analyze this problem by identifying the method of Islamization of knowledge that Luqman used to educate his son, with advice on it.